Small-size UAV design and control - Goh, Chian Kai (2017)
Miniaturization of electronics in the recent years have allowed for the production of small-sized Unmanned Aerial Vehicles (UAV) to be economically feasible. UAV with Vertical Take-Off and Landing (VTOL) capabilities have risen in popularity due to their diverse applications. These UAVs range from having two rotors to as many as eight rotors. This report will be focusing on the development of the prototype of a small-size VTOL UAV. The UAV is of the Hexa-Rotor coaxial configuration, also known as the Y6. The Y6 is a UAV with six rotors, with two rotors mounted on a single motor arm, thus being termed coaxial. Background information involving the components of the Y6 as well its aerodynamics interaction due to the coaxial configuration will be reviewed. The derivation of the dynamics of a coaxial tricopter will be shown in this report to offer an understanding of how the Y6 works. The development of the Y6 will involve the frame design using CAD software as well as the selection of multicopter components such as propellers and motors which are available in the market. The frame designed will be 3d-printed and other components purchased will be mounted onto it. The Y6 prototype will have a maximum motor to motor distance of 25cm. Initially, low-level controllers will be used for the control of the Y6. This involves tuning of the PID parameters in the lab as well as manual flight test in an outdoor environment. Subsequently, high-level controllers will be implemented for the Y6. Position information of the Y6 is obtained via a motion capture system. The information is transmitted to the Y6 in a ROS communication infrastructure. This will allow for the position control of the Y6.